Hubungan Pengawasan & Pengetahuan terhadap Perilaku Penggunaan Alat Pelindung Diri PT. Kajima Indonesia PCG Central Java Industrial Project Tahun 2025 - Ayu Widyani; Eka Cempaka Putri; Cut Alia Keumala Muda; Desyawati Utami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Work accidents in the construction sector are often triggered by workers' risky behavior in using personal protective equipment (PPE). This research aims to determine the relationship between knowledge and supervision and the behavior of using PPE in construction workers. The research method uses a quantitative approach with a cross sectional design. The number of respondents was 50 workers selected through total sampling. Data was collected using questionnaires and observations, then analyzed using the Chi-Square test. The research results showed that there was a significant relationship between knowledge and PPE use behavior (p < 0.05) and between supervision and PPE use behavior (p < 0.05). Workers with low knowledge tend to be undisciplined in the use of PPE. Consistent supervision contributes to increased worker discipline. This research confirms that knowledge and supervision influence the behavior of using PPE. Companies need to improve their PPE provision and storage mechanisms, increase the effectiveness of supervision, develop risk-based work procedures according to the type of work, involve senior workers, and enforce administrative sanctions to curb risky behavior and prevent workplace accidents.